2014
DOI: 10.1002/cmdc.201300546
|View full text |Cite
|
Sign up to set email alerts
|

3‐Aminoazetidin‐2‐one Derivatives as N‐Acylethanolamine Acid Amidase (NAAA) Inhibitors Suitable for Systemic Administration

Abstract: N Acylethanolamine acid amidase (NAAA) is a cysteine hydrolase that catalyzes the hydrolysis of endogenous lipid mediators such as palmitoylethanolamide (PEA). PEA has been shown to exert anti–inflammatory and antinociceptive effects in animals by engaging peroxisome proliferator–activated receptor–α (PPAR–α). Thus preventing PEA degradation by inhibiting NAAA may provide a novel approach for the treatment of pain and inflammatory states. Recently, 3–aminooxetan–2–one compounds were identified as a class of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…39 We did not modify the azetidin-2-one ring of ARN726, which reacts with the catalytic cysteine of NAAA, but replaced the 4-butyl-cyclohexyl group with a C9 saturated aliphatic chain bearing a terminal alkyne tag (Figure 2a). We selected a C9 chain for two reasons: first, previous work had shown that NAAA displays higher affinity for inhibitors with long aliphatic chains 33,38 and, second, we expected that such a chain would facilitate the interaction between the alkyne moiety of 1 and the azide group of the reporter tag during the click chemistry reaction. The chemical synthesis of 1 is described under Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 We did not modify the azetidin-2-one ring of ARN726, which reacts with the catalytic cysteine of NAAA, but replaced the 4-butyl-cyclohexyl group with a C9 saturated aliphatic chain bearing a terminal alkyne tag (Figure 2a). We selected a C9 chain for two reasons: first, previous work had shown that NAAA displays higher affinity for inhibitors with long aliphatic chains 33,38 and, second, we expected that such a chain would facilitate the interaction between the alkyne moiety of 1 and the azide group of the reporter tag during the click chemistry reaction. The chemical synthesis of 1 is described under Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…This program led to the discovery of 3-aminoazetidin-2-ones derivatives as potentially useful NAAA-interacting probes. 38 Within this class, ARN726 (4-cyclohexylbutyl- N -[( S )-2-oxoazetidin-3-yl]carbamate) (Figure 1) emerged as a potent, selective and systemically active NAAA inhibitor (rNAAA IC 50 = 63 nM, hNAAA IC 50 = 27 nM). 39 In vivo experiments showed that systemic ARN726 exerts pronounced anti-inflammatory effects in mouse models of carrageenan- and LPS-induced inflammation, and suppresses inflammatory reactions in human macrophages ex vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The immune regulation/paralysis could be further supported by the down-regulation of the N-acylethanolamine acid amidase ( NAAA ) and Fc fragment of IgG receptor and transporter gene ( FCGRT ), module II hub genes. NAAA degrades N-acylethanolamines in macrophages and is involved in inflammatory processes [100] and has previously been reported as potential anti-inflammatory agent [101104]. FCGRT protects immunoglobulin G from degradation, thus its expression reduced may be the result of the immune response regulatory mechanisms [105].…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, the first class of orally available NAAA inhibitors derived from the α-amino-β-lactone series has been reported. These compounds were obtained through the isosteric replacement of the β-lactone group with a β-lactam one (Fiasella et al, 2014). Among the synthesized compounds, N-[(S)-2-oxoazetidin-3-yl] nonanamide (Fig.…”
Section: Recent Advances In the Field Of Active-site-directed Naaa Inmentioning
confidence: 99%